A Method to Train Marmosets in Visual Working Memory Task and Their Performance - Nakamura, Katsuki; Koba, Reiko; Miwa, Miki; Yamaguchi, Chieko; Suzuki, Hiromi; Takemoto, Atsushi (Frontiers in Behavioral Neuroscience, 2018)
Learning and memory processes are similarly organized in humans and monkeys; therefore, monkeys can be ideal models for analyzing human aging processes and neurodegenerative diseases such as Alzheimer’s disease. With the development of novel gene modification methods, common marmosets (Callithrix jacchus) have been suggested as an animal model for neurodegenerative diseases. Furthermore, the common marmoset’s lifespan is relatively short, which makes it a practical animal model for aging. Working memory deficits are a prominent symptom of both dementia and aging, but no data are currently available for visual working memory in common marmosets. The delayed matching-to-sample task is a powerful tool for evaluating visual working memory in humans and monkeys; therefore, we developed a novel procedure for training common marmosets in such a task. Using visual discrimination and reversal tasks to direct the marmosets’ attention to the physical properties of visual stimuli, we successfully trained 11 out of 13 marmosets in the initial stage of the delayed matching-to-sample task and provided the first available data on visual working memory in common marmosets. We found that the marmosets required many trials to initially learn the task (median: 1316 trials), but once the task was learned, the animals needed fewer trials to learn the task with novel stimuli (476 trials or fewer, with the exception of one marmoset). The marmosets could retain visual information for up to 16 s. Our novel training procedure could enable us to use the common marmoset as a useful nonhuman primate model for studying visual working memory deficits in neurodegenerative diseases and aging.